KONSEP PENDIDIKAN KARAKTER MENURUT NABI IBRAHIM - Azhima, Fauzan; Silahuddin, Silahuddin (Program Studi PGSD, FKIP, Universitas Mataram, 2025)
Various character problems of the Indonesian nation are still very worrying. Various negative character facts have been shown by the Indonesian people with certain pretexts that seem to be right. The method used in this research is maudhu'i/thematic interpretation method. It is a qualitative approach. In the person of Prophet Ibrâhîm (peace be upon him), it contains the perfect human character immortalised in the Qur'ân. Among them are the Prophet Ibrâhîm as ummah, qânit, hanîf, halîm, awâh, munîb, sincere, patient, as will be discussed in the next chapter. In essence, the character possessed by the Prophet Ibrâhîm is a character to be emulated in life, especially by the leaders of this nation and society in general.